Potential of NRF2 Pathway in Preventing Developmental and Reproductive Toxicity of Fine Particles - Li, Ying-Ji; Takeda, Ken; Yamamoto, Masayuki; Kawada, Tomoyuki (Frontiers in Toxicology, 2021)
Air pollution is associated with significant adverse health effects. Recent studies support the idea that inhalation of fine particles can instigate extrapulmonary effects on the cardiovascular system through several pathways. The systemic transfer of ultrafine particles (UFPs) or soluble particle components (organic compounds and metals) is of particular concern. An integral role of reactive oxygen species (ROS)-dependent pathways has been suggested in systemic inflammatory responses and vascular dysfunction at the molecular level. Accumulating lines of evidence suggest that fine particles affect fetal development, giving rise to low birth weight and a reduction in fetal growth, and also affect the immune, cardiovascular, and central nervous systems. Oxidative stress plays an important role in fine particles toxicity; pre-treatment with antioxidants partially suppresses the developmental toxicity of fine particles. On the other hand, Nuclear factor erythroid-derived 2-like 2 (Nfe2l2), also known as NRF2, is a transcription factor essential for inducible and/or constitutive expression of phase II and antioxidant enzymes. Studies using Nrf2-knockout mice revealed that NRF2 dysfunction is intimately involved in the pathogenesis of various human diseases. Multiple single nucleotide polymorphisms (SNPs) have been detected in human NRF2 locus. An NRF2 gene SNP (−617C>A; rs6721961), located in the upstream promoter region, affects the transcriptional level of NRF2 and thereby the protein level and downstream gene expression. It has been reported that the SNP-617 is associated with various diseases. The onset and exacerbation of the diseases are regulated by genetic predisposition and environmental factors; some people live in the air-polluted environment but are not affected and remain healthy, suggesting the presence of individual differences in the susceptibility to air pollutants. NRF2 polymorphisms may also be associated with the fetal effects of fine particles exposure. Screening high-risk pregnant women genetically susceptible to oxidative stress and prevention by antioxidant interventions to protect fetal development in air-polluted areas should be considered. This article reviews the recent advances in our understanding of the fetal health effects of fine particles and describes potential chemoprevention via the NRF2 pathway to prevent the developmental and reproductive toxicity of fine particles .